Viewpoint: Agri-nutrition research: Revisiting the contribution of maize and wheat to human nutrition and health - Poole, Nigel; Donovan, Jason; Erenstein, Olaf (Elsevier, 2021)
Research linking agriculture and nutrition has evolved since the mid-20th century. The current focus is on child-stunting, dietary diversity and ‘nutrient-rich’ foods in recognition of the growing burdens of malnutrition and non-communicable diseases. This article concerns the global dietary and health contribution of major cereals, specifically maize and wheat, which are often considered not to be ‘nutrient-rich’ foods. Nevertheless, these cereals are major sources of dietary energy, of essential proteins and micronutrients, and diverse non-nutrient bioactive food components. Research on bioactives, and dietary fibre in particular, is somewhat ‘siloed’, with little attention paid by the agri-nutrition research community to the role of cereal bioactives in healthy diets, and the adverse health effects often arising through processing and manufacturing of cereals-based food products. We argue that the research agenda should embrace the whole nutritional contribution of the multiple dietary components of cereals towards addressing the triple burden of undernutrition, micronutrient malnutrition, overweight/obesity and non-communicable diseases. Agri-nutrition and development communities need to adopt a multidisciplinary and food systems research approach from farm to metabolism. Agriculture researchers should collaborate with other food systems stakeholders on nutrition-related challenges in cereal production, processing and manufacturing, and food waste and losses. Cereal and food scientists should also collaborate with social scientists to better understand the impacts on diets of the political economy of the food industry, and the diverse factors which influence local and global dietary transitions, consumer behavioural choices, dietary change, and the assessment and acceptance of novel and nutritious cereal-based products.